Ecuadorian Amazonian Fruits: A Proposal to Value Biodiversity and Promote Food Sovereignty - M Sanchez Capa; M Corell Gonzalez; C Mestanza Ramón (ESPOCH Congresses, 2023)
Abstract Fruits are characterized as a source of vitamins and minerals, recognized as an important part of a healthy eating pattern that reduces the risk of some chronic diseases. The Ecuadorian flora in the Amazon region is rich in edible fruits, but little is known about their characteristics and nutritional importance. At the same time, over the years, traditional knowledge about them has been lost. With this implication, this work pretends to describe a research proposal that values the biodiversity of edible fruits in the Ecuadorian Amazon, so that these underutilized products are conceived as more than merchandise. For this purpose, a narrative bibliographic review and a participatory observation were carried out. The research proposal included three stages i) the characterization of fruits traded in local markets; ii) an ethnobotanical study to identify the use and preference of the fruits; and iii) the analysis of bioactive compounds of at least 5 fruits prioritized according to the characterization and ethnobotanical study. The proposal stages generated research that converges the valuation of biodiversity, traditional knowledge, and nutritional potential of Ecuadorian Amazonian fruits.